Infective Substructures of Sendai Virus from Infected Ehrlich Ascites Tumor Cells - Bukrinskaya, A. G. (1968)
Increase of infectivity for embryonated eggs was observed in Ehrlich ascites tumor cells after intraperitoneal inoculation of Sendai virus into tumor-bearing mice. Virus-induced actinomycin-resistant ribonucleic acid consisting of 14S, 18S, 22S, 35S, and 48S was synthesized, and S antigen was produced in infected cells. The infectivity was suggested to be due to viral ribonucleoprotein for the following reasons: (i) the infectivity was unaffected by V antiserum but was abolished by whole hyperimmune serum, (ii) the infectivity was resistant to ribonuclease, (iii) virus particles were found neither in cells nor on red blood cell stroma treated with cellular extracts, (iv) structures similar to Sendai virus ribonucleoprotein with a maximal length of 10,500 A were observed in cellular extracts.